Alcoholic Herbal Products and Health of Peasant Adolescents in Ibadan, Nigeria (2020)
The proliferation of alcoholic herbal products (bitters, branded herbal beers and locally- produced herbal drinks) in the Nigerian public space and a corresponding high consumption rate among peasant1 adolescents has generated public health interest in recent times partly because of its associated increased social and health problems especially among young adults. However, while concerted efforts have been made to reduce alcohol consumption especially among adolescents, herbal alcohol use still remains a major problem in this group. Therefore, this article explores factors that promote utilization of alcoholic herbal drinks, perceived benefits and possible consequences associated with it. Qualitative method of data collection was adopted; In-depth interviews were conducted with 23 users (aged 15-19 years) and 12 vendors (aged 20-35 years) of herbal alcohol in purposively selected sites. Data were analyzed following the principles of theme identification and content analysis. Three themes identified were; drivers, benefits and likely consequences of herbal alcohol consumption and were found to operate through a system of normative behaviour, beliefs and experiences. The drivers of normative behaviour were: (sub) Cultural acceptance, as implied in the local and customized names used in the advert and promotion of herbal alcohol consumption which are blended in indigenous symbolic understandings; the relative availability, consumer purchasing power as well as functionality. The perceived benefits identified by users included sexual enhancement, treatments/cure for myriad of diseases and also recreation/sociation. The health and social consequences associated with misuse of alcoholic herbal products were largely neglected by both users and vendors. These have public health implications on the peasant adolescents, thus of significant interest to public health practitioners and policy-makers.